Implementation of Activity-Based Costing to Improve Profitability - Parindingan, Frivaldo Yesbarianus; Fathirah, Dian; Usman, Asri; Mediaty, Mediaty (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the application of Activity Based Costing (ABC) to improve the efficiency of cost management in the manufacturing, service, and SME sectors. A literature study was conducted using the field charting method on 21 articles published between 2012-2020. This process identified the advantages of ABC over conventional methods in avoiding cost distortions and providing accurate data for budgeting. The research examined the characteristics of activities in various categories of companies, finding that Unit and Product Level Activity are more commonly applied than Batch and Facility Level Activity. The results show the flexibility of ABC in adjusting the scale of operations, resulting in significant benefits in cost control and resource optimization, thus providing positive implications for business efficiency across sectors.